Effect of Journal Misalignment on the Static Characteristics of Porous Journal Bearings Lubricated with Couple Stress Fluid - Abd Al-shaheed, Lekaa’ H. (Al-Khwarizmi Engineering Journal, 2012)
In this paper, a theoretical study to the effect of journal misalignment on the static characteristics of oil filled porous journal bearing when lubricated with couple stress fluid has been carried out. The analytical model used through this work is for a bearing with isotropic permeability. Considering isotropic permeability the Reynolds’ equation for the oil film is modified to include a so – called filter term and the effect of fluid coupled stress. The pressure equation for the porous medium is obtained from Darcy’s law and continuity equation. The equation which was used to evaluate the oil film thickness was modified to include the effect of possible misalignment in longitudinal and transverse directions. The governing equations with appropriate boundary conditions are numerically solved using a suitable numerical technique. A computer program has been prepared to solve the governing equations. The validity of the program has been tested by comparing the results obtained through this work with that published in available works. The comparison shows a good agreement between the results obtained through this work and that published by other workers. By comparing the behavior of aligned and misaligned bearing it was found that the journal center misalignment has a considerable effect on the performance parameters of the bearing which can not be neglected.